Thin vulvar melanoma: a challenging diagnosis. Dermoscopic features of a case series. (1st March 2020) - Vaccari, S.; Barisani, A.; Salvini, C.; Pirola, S.; Preti, E. P.; Pennacchioli, E.; Iacobone, A. D.; Patrizi, A.; Tosti, G.
Summary: Background: Vulvar melanoma (VM) is rare and is often diagnosed late. Dermoscopy may aid in its recognition, differentiating VM from other more common vulvar lesions, such as melanosis and naevi. However, little is known about the dermoscopic features of thin VM. Aim: To retrospectively analyse a series of histopathologically diagnosed thin VMs and to highlight their most suggestive dermoscopic features. Methods: A multicentre, retrospective study was conducted, including histopathologically proven thin VMs, either intraepidermal or with Breslow thickness ≤ 0.5 mm, diagnosed during the period 2016–2018. We particularly focused on their dermoscopic characteristics to highlight the most suggestive dermoscopic diagnostic clues. Results: In total, 14 cases of early‐stage VM were included, in women with a mean age at diagnosis of 64.86 years. The most frequently affected sites were the labia minora. Of these, 11 cases were unifocal. Dermoscopy most often revealed structureless areas, grey globules and areas, irregular black–brown dots, blue and white structures, and red areas. Conclusions: In our experience, early‐stage VM often exhibits dermoscopic features that are more typical of thicker cutaneous melanomas. Dermoscopy may provide useful clues for the prompt diagnosis of thin VM.